Neighborhood story. 4 - Yazawa, Ai (Shojo beat manga., 2024)
"After winning the Grand Prix award at the Yaza Arts Fashion Show, Mikako and Risa are offered the chance to study abroad in London for a year and a half with all expenses covered. As the initial thrill wanes, however, Mikako’s apprehensions grow, especially with the potential strain that leaving might put on her relationship with Tsutomu. Meanwhile, Ruriko is feeling sick, and everyone fears a relapse in her condition. After Ruriko receives a shocking diagnosis, Mikako is forced to reexamine her decision. Will she stay behind and choose love, or follow her passion and make her dreams of being a famous fashion designer finally come true in London?"